Assessments of Vibrio parahaemolyticus and Vibrio vulnificus levels and microbial community compositions in blue crabs (Callinectes sapidus) and seawater harvested from the Maryland Coastal Bays - Smalls, Jasmine; Grim, Christopher; Parveen, Salina (Frontiers in Microbiology, 2023)
Introduction Fluctuations in environmental physicochemical parameters can affect the diversity and prevalence of microbial communities, including vibrios, associated with aquatic species and their surrounding environments. This study aimed to investigate the population dynamics of two Vibrio species as well as the microbial community diversity of whole crab and seawater from the Maryland Coastal Bays (MCBs), using 16S rRNA sequencing. Methods During this study, three crabs and 1 L of seawater were collected monthly from two sites for 3 months. Crab tissue was extracted and pooled for each site. Extracted crab tissue and seawater were analyzed for Vibrio parahaemolyticus and V. vulnificus using Most Probable Number (MPN) real-time PCR. For 16S rRNA microbiome analysis, three different DNA extraction kits were evaluated to extract microbial DNA from individual crabs. Also, 500 mL of each seawater sample was filtered for DNA extraction. Results Results indicated that sample types and sampling periods had a significant effect on the alpha diversity of the microbial community of crabs and seawater (p < 0.05); however, no statistical difference was found between DNA extraction kits. Beta diversity analysis also found that the microbial compositions between sample types and temporal distributions were statistically significant. Taxonomic classification revealed that Proteobacteria, Cyanobacteria, Actinobacteria, and Bacteroidetes were present in both crab and seawater samples. Vibrio parahaemolyticus and V. vulnificus were also detected in both crab and seawater samples, although crabs contained a higher concentration of the bacterium compared to the seawater samples. It was found that vibrios were not a dominant species in the microbial community of crab or seawater samples. Discussion Results from this study provide further insight into species diversity and phylogenetic compositions of blue crabs and seawater from the MCBs. These approaches will help in risk assessments that are essential in the overall advancement of public health.